DETERMINATION OF TOLERANCE LEVELS IN RADIOTHERAPY DOSIMETRY BASED ON STATISTICAL INTERFERENCE - Koniarová, Irena; Kotík, Lukáš (Radiation protection dosimetry, 2019)
The most important dosimetry quantity that is determined at radiotherapy centers is the absorbed dose to water for external beams. Fixed tolerances for absorbed doses measured under reference conditions with an ionization chamber for high-energy photon and electron beams are usually 2 and 3%, respectively, regardless of uncertainties of the input variables and other conditions during evaluation. In reality, this agreement should be evaluated considering the uncertainties of the input variables because they affect the size of the random deviations of the measurements from their true values. The aim of this work was to develop a new approach to evaluate the agreement between measured and reported values based on statistical interference rather than to use fixed tolerance levels. The proposed method considers different scenarios that can occur during the evaluation of agreement. Because the method is described in general, it can be used in all similar situations when partial uncertainties can be established.
Keywords: celková dávka radioterapie; nejistota; Radiotherapy, Intensity-Modulated; Radiotherapy Dosage; Uncertainty; nádory; radioterapie s modulovanou intenzitou; Radiotherapy, High-Energy; plánování radioterapie pomocí počítače; lidé; Neoplasms; statistické modely; Calibration; Humans; kalibrace; Models, Statistical; vysokoenergetická radioterapie; Radiotherapy Planning, Computer-Assisted